Simbolisme, Realitas, dan Pikiran dalam Semiotika Charles W. Morris - Patrio Tandiangga (CV. Syntax Corporation Indonesia, 2021)
The purpose of this research is to discuss the problem of the nature of the mind, the place of mind in experience, and the relation of mind and experience to reality at large. Morris aims to show that thought and mind are not entities, nor even processes involving a physical substance distinguishable from the rest of reality, but are explicable as the functioning of parts of experience as symbol to an oganism of other parts of experience. Being then the symbolic portion of experience, the physical or mental can neither be sharply opposed to the rest of experience nor identified with the whole of experience. Since experience will be shown to be a portion of reality, it follows that mind and reality can never be utterly separated nor indiscriminately identified. A functional view of mind gives a new basis for the interpretation of philosophical problems.